THE READINESS OF THE GOVERNMENT INTERNAL SUPERVISORY APPARATUS (APIP) FOR CONTINUOUS AUDITING IMPLEMENTATION - Amrie Firmansyah; Dina Khairunnisa; Tyara Laritza Gistiani; Putri Rieza Chaniago (Polytechnic of State Finance STAN, 2023)
Various countries are transforming in responding to the Industrial 4.0 Era, where technology plays an important role in various activities. The government sector is also not spared from this phenomenon and responds to industrial developments by transforming business processes that were previously manual to computerized through e-government. As the government's internal supervisor, the Government Internal Supervisory Apparatus (APIP) needs to transform into utilizing technology and increase capabilities in the technology field in providing relevant added value through improving government performance to increase public trust. The use of technology by APIP is currently being developed towards continuous auditing to provide early warning of problems that can hinder the achievement of organizational goals. This study aims to review the readiness of APIP in response to Continuous Auditing implementation. This study uses primary data through a survey of respondents from Indonesia's National Government Internal Auditor (BPKP) and the Inspectorate General of the Ministry of Finance with a total sample of 32 respondents. Research data analysis was carried out using descriptive statistics. This research concludes that most APIPs are ready to implement CA, although some APIPs still have problems preparing them.